Gender justice and social inclusion of female learners with dwarfism: A case study in Bindura District, Zimbabwe - Muchabaiwa, Wonder; Matope, Nogget; Moyo, Annah (S&Co Publishing, 2025)
This study explored social exclusion challenges experienced by female secondary school learners with dwarfism in Bindura district, Mashonaland Central province, Zimbabwe. The qualitative study used a case study research design. The study's participants were two learners with dwarfism, two administrators, four teachers, and 12 learners (who are not dwarves but attend classes with the learners with dwarfism). The participants were purposively selected because of their experiences with the phenomenon under study. Data were collected through in-depth interviews and focus group discussions. Findings revealed that learners with dwarfism have problems that begin as a result of their small stature, socially constructed as a disability by society. Other challenges include inappropriate infrastructure and furniture, stigmatization, and segregation in sporting activities. However, female learners with dwarfism face peculiar challenges because of their gender. These challenges include sexual harassment and the burden of stereotyped feminine chores in the school. The findings revealed that gender and disability remain exclusionary, and oppressive systems that affect the schooling experiences of female learners with dwarfism disproportionately. The study recommends that schools adopt an inclusive education policy that addresses issues of exclusion based on gender and disability.